Technology Acceptance Model, Social Influence and Perceived Risk in Using Mobile Applications: Empirical Evidence in Online Transportation in Indonesia - Ikhsan, Khairul (JDM (Jurnal Dinamika Manajemen), 2020)
The purpose is to examine the impact of technology acceptance model consisting of usefulness and ease of use on the intention to use, social influence and perceived risk consisting of physical and psychological risk on the intention to use, and examine its impact on behavior using mobile applications. Benefit, ease of use and social factors were considered as the critical factors in accepting and using a technology. However, mobile applications has limitation in consuming an online product or service. A total of 1383 questionnaires were obtained from respondents of online transportation service users in Jakarta, Bandung, Yogyakarta and Surabaya. Using PLS-SEM, it is found that the there are significant relationships between technology acceptance model, physical risk, intention and behavior using mobile applications, but no relationship between psychological risk and intention. This study also found that the influence of intention on behavior using mobile applications is dependent on perceived usefulness, perceived ease of use and perceived physical risk rather than perceived psychological risks.